Novel Interprofessional Mentoring Intervention to Improve Spirometry in Primary Care: Uptake, Feedback, and Effects on Behavioral Intention. Issue 3 (2017) - Gupta, Samir; Allen, Christopher; Moosa, Dilshad; MacPherson, Ana; Tamari, Itamar E.
Abstract : Introduction: Little is known about the nature and effects of mentoring interventions on evidence-based clinician behaviors. We sought to design and evaluate a novel mentorship-based intervention to improve the usage of spirometry in primary care. Methods: This was a prospective one-year study of a pragmatic intervention across Canadian primary care sites. We established mentor–mentee pods, each including physician and nurse/allied health mentors and mentees, and enabled communication through a secure online portal; email; telephone; teleconference; videoconference; fax; and/or in person. We measured (1) change in intention to perform spirometry (through a questionnaire based on the theory of planned behavior, administered before and after the intervention); (2) mentoring uptake; and (3) feedback/satisfaction. Results: Twenty-five of 90 (28%) nurse/allied health and 23/68 (34%) physician mentees consented across seven sites. There were no statistically significant changes in behavioral intention after the intervention. Mentors logged 56.5 hours, with most preferred communication modalities being in person (6/11; 55%) and email (4/11; 36%). Mentees most commonly used email (9/18; 50%), followed by in-person communication (6/18; 33%). Mentees were highly satisfied with the experience, and most (89%) would participate in a similar program again. Discussion: A mentorship-based intervention can successfully engage physicians, nurses, and allied health practitioners through multiple communication platforms. Email seems to be an important medium for this activity. Such interventions can be highly satisfying and may affect certain constructs underlying mentees' behavioral intentions. Such a program can be replicated across diseases, and future research should measure effects on behavior, patient outcomes, and the sustainability of effects.